The Bifurcations of Traveling Wave Solutions of the Kundu Equation. (1st October 2013) - Yi, Yating; Liu, Zhengrong
Abstract : We use the bifurcation method of dynamical systems to study the bifurcations of traveling wave solutions for the Kundu equation. Various explicit traveling wave solutions and their bifurcations are obtained. Via some special phase orbits, we obtain some new explicit traveling wave solutions. Our work extends some previous results.